Exploring the efficacy of media literacy on online political participation of learners in adult and vocational education in Nigeria - Okop, Ekaette Okon; Oroka, Othuke Valentine; Ladan, Babangida; Olori, Christian Nwachukwu; Olori, Gloria Iniobong; Okanazu, Oliver Okechukwu; Nwizu, Stella Chioma; Nwachukwu, Ruphina Ukamaaka (Faculty of Social and Political Science, Universitas Airlangga, 2025)
The benefits of Information and Communication Technology (ICT) in societal growth are well-documented; however, its application in developing countries such as Nigeria has been limited due to a lack of knowledge. This study investigates media literacy’s impact on learners’ online political participation in adult and vocational education in Nigeria. It adopted a non-equivalent control type of quasi-experimental research design involving experimental and control groups. The sample consisted of 196 learners selected from public adult and vocational education centers across Nigeria. The “Online Political Participation Test” (OPPT) was the data collection instrument. The findings indicate that the mean online political participation scores of learners trained in media literacy did not differ significantly from those trained in basic literacy. Additionally, the mean online political participation scores of learners using cooperative learning styles were not significantly different from those using solitary learning styles. Regarding the interaction effects, there were no significant differences in the mean online political participation scores based on the learning styles adopted by the learners. The study concluded that basic literacy had a more positive impact than media literacy in informal learning environments in developing countries.